Effectiveness of telbivudine antiviral treatment in patients with hepatitis B virus-associated glomerulonephritis: A 104-week pilot study. Issue 31 (August 2018) - Yan, Zhaoping; Qiao, Bing; Zhang, Haifeng; Wang, Yanling; Gou, Wei
Abstract : Abstract: The aim of this study was to evaluate clinical efficacy of telbivudine in treatment of hepatitis B virus-associated glomerulonephritis (HBV-GN). A total of 43 HBV-GN patients combined with chronic hepatitis B were treated with telbivudine for 104 weeks. Serum levels of HBV DNA viral load, HBeAg, HBeAb, alanine aminotransferase (ALT), aspartate aminotransferase (AST), serum creatinine (Cr), and 24-hour urinary protein were evaluated after telbivudine treatment of 12, 24, 52, 76, and 104 weeks. Estimated glomerular filtration rate (eGFR) was calculated at baseline, 24 weeks, 52 weeks, and 104 weeks of treatment, respectively. Complete remission (CR) was defined as urinary protein <0.3 g/day, with normal ALT, AST, Cr, and eGFR. Criteria for partial remission include: 24-hour urinary protein excretion decreased by >50% compared with baseline level, and ALT and AST decreased >50%. Proteinuria level gradually decreased in patients with HBV-GN after telbivudine treatment. The percentages of PR + CR were 90.7% and 95.3%, respectively, at 52 and 104 weeks. Compared to baseline, eGFR were significantly increased from 69.2 ± 23.1 mL/min/1.73 m 2 to 116.2 ± 26.3 mL/min/1.73 m 2 at 104 weeks of treatment. Multivariate analysis indicated that baseline HBV DNA viral load (odds ratio [OR] = 1.19, 95% confidence interval [CI] 1.11–2.19, P  = .02) and baseline urinary protein (OR = 1.08, 95% CI 1.04–2.44, P  = .03) were independent risk factors associated with CR after telbivudine treatment among patients with HBV-GN. Our study demonstrates that telbivudine can be used to treat HBV-GN and effectively improve eGFR in these patients.